2015
DOI: 10.1007/978-3-319-25554-5_21
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Gaze in Human-Robot Collaborative Assembly

Abstract: In this paper we explore how social gaze in an assembly robot affects how naïve users interact with it. In a controlled experimental study, 30 participants instructed an industrial robot to fetch parts needed to assemble a wooden toolbox. Participants either interacted with a robot employing a simple gaze following the movements of its own arm, or with a robot that follows its own movements during tasks, but which also gazes at the participant between instructions. Our qualitative and quantitative analyses sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Solutions so far focus on limited applications and do not provide a complete system [7]. Smart factories, as also presented in this article, do not exit yet [8] due to the social impact [9].…”
Section: Introductionmentioning
confidence: 95%
“…Solutions so far focus on limited applications and do not provide a complete system [7]. Smart factories, as also presented in this article, do not exit yet [8] due to the social impact [9].…”
Section: Introductionmentioning
confidence: 95%
“…Since persuasive attempts potentially limit people's decisional freedom, they might trigger feelings of anger (towards the persuader), and cause people to host negative thoughts (about the persuader), and in some cases even motivate them to do the opposite to what they are asked to do [19,20]. Earlier research [20][21][22] has shown that psychological reactance can be measured using questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…While much of our work presented in this paper is focussed on robot learning gesture-action associations, we also studied how the gaze of the robot was perceived by the participants of our user study. Building on prior research (Ruesch et al, 2008 ; Bee et al, 2009 ; Fischer et al, 2015 ), we used the gaze of the robot to indicate the action it is about to perform and to indicate when it is ready for the next instruction. The study by Huang et al ( 2015 ) demonstrates how a robot can facilitate a collaborative task by observing human gaze cues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown how gaze can serve to indicate the readiness of the robot (Bee et al, 2009 ) or to signal planned actions followed by an action (Huang et al, 2015 ). In the work by Fischer et al ( 2015 ), the authors explore the effects of social gaze in a collaborative toolbox assembly scenario with naive users. Their analyses show that a robot with active gaze engages people faster compared to the one without it.…”
Section: Introductionmentioning
confidence: 99%